Caracterização morfofisiológica e dormência de sementes de oliveira (Olea europaea L.) - Ribeiro, Bárbara Gomes (2020)
The olive tree (Olea europaea L.) is one of the oldest fruit trees in the world. Its origin got lost in time and mixes with the evolution of civilizations. The first researches realized in Minas Gerais are dated in 2008 by the Empresa de Pesquisa Agropecuária de Minas Gerais (EPAMIG) in the municipality of Maria da Fé. There are 40 municipalities in Minas Gerais which are involved in the production of olives and everything points that, in the mid- to long-term, Brazil becomes a major producer. For that, researches involving the propagation and selection of more adapted cultivars to our regions are important. The olive tree is multiplied on large scales through stakes. However, the success of the cutting depends on the capability to form roots. For some cultivars, this is a great obstacle. In order to overcome this problem, the grafting technique has been used, and rootstocks are obtained through seeds, however, the seed germination is a huge bottleneck, due to the presence of a hard endocarp and the hypothesis of the presence of dormancy in the olive seeds. Thus, the objective of this work was to characterize olive cultivars, as well as to study alternatives to overcome seed dormancy. Fruits of four olive cultivars were used, Arbequina, Ascolano 315, Koroneiki and Maria da Fé, harvested in Maria da Fé - MG, in 2017. The image analysis of fruits, endocarps and seeds were done using the X-rays and the Ground-Eye®, in addition to the physiological evaluation of seedlings. Also, molecular analysis was performed through DNA analysis, using the ISSR molecular marker. For the study of dormancy, stratification and scarification of endocarps of olive seeds were carried out. Is was used for the experiments the gibberellic acid (GA3) and sulfuric acid (H2SO4) at different periods and concentrations, and also different periods of exposure of endocarps and seeds to cold (10ºC). After the exposure to treatments, endocarps and seeds were submitted to the germination test and compared with the control. It was possible to differentiate the cultivars by image analysis. The variables of geometry are the ones that best distinguished the cultivars by analyzing the endocarp. Regarding seeds, the evaluation of the color allowed a better cultivar differentiation. Genetic analysis was also efficient for characterizing the cultivars. Through the dendrogram it was possible to visualize a low genetic similarity between the cultivar Arbequina with the others. For scarification and stratification treatments, the cultivars studied did not respond in a similar way. The germination of olive endocarps from the cultivars Arbequina, Koroneiki and Maria da Fé, was possible when submitted to H2SO4 for 18 hours. However, the use of H2SO4 itself did not allowed the germination of endocarps, requiring stratification of them combined with GA3. Stratification for 30 days allowed an increased germination of the endocarps of the cultivars Arbequina, Ascolano 315, Koroneikie and Maria da Fé, indicating that the dormancy of olive seeds is physical and physiological.